Effects of repeated bouts of soccer-specific intermittent exercise on salivary IgA - Sari-Sarraf, V.; Reilly, T.; Doran, D.; Atkinson, G. (International Journal of Sports Medicine, 2008)
Failure to recover fully between sessions has been suggested to cause immunodepression. Therefore, the cumulative effects of soccer-specific intermittent exercise undertaken on different days 48 h apart on salivary IgA, cortisol and total protein concentration were investigated. Nine male subjects completed two trials of soccer-specific intermittent exercise 48 h apart on a motorised treadmill. Timed unstimulated saliva samples were collected immediately before and after exercise, and 24 and 48 h post-exercise. Salivary IgA concentration (EX1: 215 ± 160 to 335 ± 246 and EX2: 144 ± 93 to 271 ± 185 mg · l-1, p = 0.007), osmolality (p = 0.001) and total protein (p = 0.001) increased immediately following exercise in both trials and decreased 24 h afterwards, whereas saliva flow rate decreased significantly (p = 0.015) before returning to pre-exercise values 24 h postexercise. The IgA secretion rate, IgA to osmolality ratio, IgA to total protein, solute secretion rate, total protein secretion rate, and cortisol did not differ between the time-points. The results suggest that performing two bouts of moderate intensity soccer-specific intermittent exercise 48 h apart does not suppress resting salivary IgA concentration significantly although a small progressive reduction in salivary IgA was observed. These findings may not extend to successive competitive soccer games when vulnerable players might experience clinically relevant reductions in s-IgA.